Reflection on Indonesia's PISA Scores and the 2024 Madrasah Teacher Competency Assessment Results: Challenges in Enhancing Teacher Competence - Achmad Zukhruf Alfaruqi; Nurwahidah Nurwahidah (JURNAL PENDIDIKAN IPS, 2025)
The low score of Programme for International Student Assessment (PISA) of Indonesian students in 2022 is a serious concern in education. PISA results show that Indonesian students' literacy, numeracy and science skills are still below the international average. One of the factors contributing to this problem is the suboptimal quality of teachers. Based on the results of the Assessment of the Competence of Madrasah Teachers and Education Personnel in 2024, it was found that many teachers still have limitations in pedagogic, literacy and numeracy aspects. This study aims to analyse the relationship between the low PISA scores of Indonesian students and the quality of teacher competence through a descriptive approach. Using a descriptive quantitative approach, this study processes secondary data from the results of teacher competency assessments covering pedagogic, professional, social, and personality aspects. The results show that there is a significant relationship between low teacher competence and student academic achievement. Some of the main points found were weak mastery of higher-order thinking skills (HOTS)-based learning concepts, lack of innovation in learning methods, and minimal utilisation of technology in the teaching process. In addition, many teachers do not have effective strategies to improve students' literacy and numeracy skills. Efforts to improve the quality of education in Indonesia require more comprehensive policies, including strengthening teacher training, periodic evaluation and improving the welfare of educators.